USE OF TECHNOLOGICAL RESOURCES IN SCIENCE EDUCATION: PRODUCTION OF VIDEO EXPERIMENTAL LESSONS BY FUTURE TEACHERS - Souza Filho, Moacir Pereira de; Souza, Agda Eunice de [UNESP]; Gibin, Gustavo Bizarria [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2017)
This article presents a survey conducted in an extension course that integrates science education (experimental activities) and media (production video lessons). The methodology used was the Textual Analysis Discourse that investigated the concepts of future teachers of Physics and of Chemistry about the potential of producing an instructional video to students and teachers. The results showed that the video lesson is in a new teaching approach (active methodology), that touches the senses (motivates), which promotes the learning of concepts (the language), the resourcefulness of the participants before the cameras and promotes the democratization of knowledge (internet).
Keywords: Media; Science teaching; Teacher training